Inference of facultative mobility in the enigmatic Ediacaran organism Parvancorina - Darroch, S; Rahman, I; Gibson, B; Racicot, R; Laflamme, M (Royal Society, 2017)
Establishing how Ediacaran organisms moved and fed is critical to deciphering their ecological and evolutionary significance, but has long been confounded by their non-analogue body plans. Here, we use computational fluid dynamics to quantitatively analyze water flow around the Ediacaran taxon Parvancorina, thereby testing between competing models for feeding mode and mobility. The results show that flow was not distributed evenly across the organism, but was directed towards localized areas; this allows us to reject osmotrophy, and instead supports either suspension feeding or detritivory. Moreover, the patterns of recirculating flow differ substantially with orientation to the current, suggesting that if Parvancorina was a suspension feeder, it would have been most efficient if it was able to re-orient itself with respect to current direction, and thus ensure flow was directed towards feeding structures. Our simulations also demonstrate that the amount of drag varied with orientation, indicating that Parvancorina would have greatly benefited from adjusting its position to minimize drag. Inference of facultative mobility in Parvancorina suggests that Ediacaran benthic ecosystems might have possessed a higher proportion of mobile taxa than currently appreciated from trace fossil studies. Furthermore, this inference of movement suggests the presence of musculature or appendages which aren’t preserved in fossils, supporting a bilaterian affinity for Parvancorina.